6Ps-based instructional model: An innovative framework for supporting organic chemistry education through a multimedia-supported flipped classroom approach - Nsabayezu, Ezechiel; Habimana, Olivier; Nzabalirwa, Wenceslas; Niyonzima, Francois Niyongabo (Discover education, 2025)
In response to the persistent challenges students face in mastering complex scientific concepts, innovative instructional approaches are needed to improve learning outcomes and engagement. Thus, this study presents the newly designed 6Ps-based instructional model aimed at enhancing organic chemistry education through a multimedia-supported flipped classroom approach. Guided by the Design-Based Research (DBR) methodology, this study began with a comprehensive literature review to identify gaps in the application of flipped classroom strategies and multimedia integration within organic chemistry education. The findings informed the development of the 6Ps-based instructional model, designed in collaboration with chemistry subject experts, instructional designers, experienced secondary school teachers, and students. This collaborative and iterative design process ensured both theoretical grounding and practical relevance. The initial version of the model was piloted in selected secondary schools, where participating chemistry teachers implemented it in real classroom environments. To evaluate its effectiveness, data were collected through Likert-scale questionnaires, semi-structured interviews, achievement test, and classroom observations, focusing on key indicators such as student engagement, motivation, conceptual understanding, and instructional quality. Feedback from this phase guided several refinements to enhance instructional strategies and the integration of multimedia resources. A subsequent implementation confirmed notable improvements in student participation, collaboration, and motivation. The finalized model consists of six interconnected phases, each represented by the letter “P,” (1) Plan the curriculum ensures a structured and coherent content sequence, while (2) Produce multimedia content simplifies complex concepts through digital resources. (3) Provide pre-class assignments promotes guided learning, and (4) Promote interactive in-class activities fosters active student engagement. (5) Perform post-class assessments reinforces learning through structured exercises and feedback, while (6) Pursue continuous improvement ensures ongoing refinement based on student feedback and research insights. The study confirms the model’s effectiveness in making organic chemistry more accessible and engaging. Thus, future research can further explore its adaptability to other STEM disciplines, broadening its impact on science learning.